Genetic differentiation of the regional Plutella xylostella populations across the Taiwan Strait based on identification of microsatellite markers. Issue 24 (1st December 2015) - Ke, Fushi; You, Shijun; He, Weiyi; Liu, Tiansheng; Vasseur, Liette; Douglas, Carl J.; You, Minsheng
Abstract: Movement of individuals through events, such as storms or crop transportation, may affect survival and distribution of insect pests, as well as population genetic structure at a regional scale. Understanding what factors contribute to gene flow in pest populations remains very important for sustainable pest management. The diamondback moth ( Plutella xylostella ) is an insect pest well known for its capacity of moving over short to long distances. Here, we used newly isolated microsatellite markers to analyze the genetic structure of nine populations across the Taiwan Strait of China (Taiwan and Fujian). A total of 12, 152 simple sequence repeats (SSRs) were initially identified from the P. xylostella transcriptome (~94 Mb), with an average of 129 SSRs per Mb. Nine SSRs were validated to be polymorphic markers, and eight were used for this population genetic study. Our results showed that the P. xylostella populations could be divided into distinct two clusters, which is likely due to the year‐round airflows in this region. A pattern of isolation by distance among the local populations within Fujian was found, and may be related to vegetable transportation. Considering the complexity of the P. xylostella population genetic structure from local and regional to global levels, we propose that developing ecologically sound strategies for managing this pest will require knowledge of the link between behavioral and population ecology and its genetic structure. Abstract : Our results showed that the P. xylostella populations could be divided into two distinct clusters, which is probably due to the year‐round airflows across the Taiwan Strait.